Immunization With Recombinant Chaperonin60 (chp60) Outer Membrane Protein Induces A Bactericidal Antibody Response Against Neisseria Meningitidis - Renee Phillips; Jeannette N Williams,; Wei-Ming Tan,; Magdalena K Bielecka,; Hannah Thompson,; Miao-Chiu Hung,; John E Heckels,; Myron Christodoulides (Elsevier, 2024)
Sera from individuals colonized with Neisseria meningitidis and from patients with meningococcal disease contain antibodies specific for the neisserial heat-shock/chaperonin (Chp)60 protein. In this study, immunization of mice with recombinant (r)Chp60 in saline; adsorbed to aluminium hydroxide; in liposomes and detergent micelles, with and without the adjuvant MonoPhosphoryl Lipid A (MPLA), induced high and similar (p>0.05) levels of antibodies that recognized Chp60 in outer membranes (OM). FACS analysis and immuno-fluorescence experiments demonstrated that Chp60 was surface-expressed on meningococci. By western blotting, murine anti-rChp60 sera recognized a protein of Mr 60kDa in meningococcal cell lysates. However, cross-reactivity with human HSP60 protein was also observed. By comparing translated protein sequences of strains, 40 different alleles were found in meningococci in the Bacterial Isolate Genome Sequence database with an additional 5 new alleles found in our selection of 13 other strains from colonized individuals and patients. Comparison of the non-redundant translated amino acid sequences from all the strains revealed ≥97% identity between meningococcal Chp60 proteins, and in our 13 strains the protein was expressed to high and similar levels. Bactericidal antibodies (median reciprocal titres of 32-64) against the homologous strain MC58 were induced by immunization with rChp60 in liposomes, detergent micelles and on Al(OH)3. Bactericidal activity was influenced by the addition of MPLA and the delivery formulation used. Moreover, the biological activity of anti-Chp60 antisera did not extend significantly to heterologous meningococcal strains. Thus, in order to provide broad coverage, vaccines based on Chp60 would require multiple proteins and specific bactericidal epitope identification.